Konsep Tazkiyat Al-Nafs Al-Ghazali Sebagai Metode Dalam Pendidikan Akhlak - Ayu Wandira, Muhammad Saleh, Ahmad Fuadi (Khazanah : Journal of Islamic Studies, 2023)
In this study the author presents the concept of tazkiyat al-nafs according to Al-Ghazali in his book Ihya Ulumuddin to be used as a benchmark as a method in moral education. This research is a library research. Data analysis was carried out by means of inductive-deductive, comparative, descriptive and interpretive. The results of the study explain that to purify oneself or the soul, according to Imam Al-Ghazali, it is necessary to carry out the process of takhalli (self-emptying of reprehensible qualities), tahalli (filling oneself with praiseworthy qualities) and tajalli (a feeling of full devotion to God/self-serving). to Allah). Al-Ghazali put forward ten concepts of tazkiyatun nafs in the context of education, namely: prioritizing the purity of the soul over despicable morals, reducing relations with the busy world, willing to stay away from family and homeland to study knowledge, not arrogant because of knowledge and not opposing teachers, keeping oneself from listening to different human opinions, not abandoning commendable sciences, acquiring knowledge gradually, knowing the reasons for knowing the glory of knowledge, and knowing the relationship between science and its goals. The relevance of Imam Al-Ghazali's thoughts about the tazkiyat al-nafs method with moral education in schools is still relevant theoretically, this is because there are still many educational materials that still use his concept, namely tazkiyat al-nafs is an effort to cleanse the soul by do commendable deeds so that he is close to Allah.